2021
DOI: 10.1177/1538574421994417
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Endovascular Treatment of Portal Vein Stenosis in Liver Transplant Recipients: A Systematic Review

Abstract: Purpose: To evaluate the efficacy of Angioplasty and Stent Placement for the treatment of Portal Vein Stenosis in Liver Transplant Recipients by performing a systematic review. Materials and Methods: The PubMed Database was extensively searched for articles describing Portal Vein Stenosis (PVS) as a complication in Liver Transplant (LT) patients. The initial database search yielded 488 unique records published in the PubMed Database, 19 of which were deemed to meet the inclusion criteria. Outcomes were separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
7
0
3
Order By: Relevance
“…This is in line with a recent systematic review of 243 pediatric patients: primary PTSA has higher technical success and lower restenosis rates (2.5% vs. 29.7%) compared with PTBA alone. [31] Notably, in our cohort, almost half of the patients (19/40) successfully received PTSA within 6 months after LT and 6 within 45 days after LT (PTSA n = 4; PTBA n = 2). PVS early after LT is often more elastic, and PTBA alone might be ineffective and more prone to a possible vessel tear at the anastomotic site.…”
Section: Technical and Clinical Success Complications Of Primary Ptsamentioning
confidence: 73%
See 1 more Smart Citation
“…This is in line with a recent systematic review of 243 pediatric patients: primary PTSA has higher technical success and lower restenosis rates (2.5% vs. 29.7%) compared with PTBA alone. [31] Notably, in our cohort, almost half of the patients (19/40) successfully received PTSA within 6 months after LT and 6 within 45 days after LT (PTSA n = 4; PTBA n = 2). PVS early after LT is often more elastic, and PTBA alone might be ineffective and more prone to a possible vessel tear at the anastomotic site.…”
Section: Technical and Clinical Success Complications Of Primary Ptsamentioning
confidence: 73%
“…[8,[10][11][12][13]30] However, most of these studies reported combined balloon and stent angioplasty data and PV diameters are often not reported. In a recently published systemic review of the literature, Sare et al [31] concluded that primary PTSA had technical success of 100%, which was significantly higher compared with balloon angioplasty. They clearly favored primary stent implantation as treatment of choice.…”
Section: Technical and Clinical Success Complications Of Primary Ptsamentioning
confidence: 99%
“… 91 Primary stent placement was also shown to have a significantly higher success rate than balloon angioplasty (97–100% vs. 67–69%) in a recent meta-analysis. 92 …”
Section: Portal Vein Recanalisationmentioning
confidence: 99%
“…Although balloon angioplasty could be utilized in these patients, due to postsurgical fibrotic changes, re-stenosis and need for a second procedure is high. A recent systematic review of 393 patients who had interventional treatment due to portal vein stenosis after liver transplantation showed higher technical success and lower re-stenosis rates after primary stenting in relation to angioplasty alone [47].…”
Section: Portal Vein Interventionsmentioning
confidence: 99%